Discursive identity battle and the reformation of organisational identity in an M&A process - Kastarinen, Arja; Vesanen, Elisa (2014)
This study explores the evolution of organisational identity in a post-merger integration process, applying a hybrid of social actor perspective and social constructionist framework on the organisational identity development. The findings show how the new shared identity of the two merging Finnish companies, operating within an international group, is formed through a discursive battle between the respective organisational identities. The case indicates, how various types of dialectical tensions arise from the organisational identity legitimation endeavours in a merger context and the path-dependent nature of these tensions. It shows the importance of sustaining part of the previous organisational identity, a continuity of identity, and maintaining the power balance between the merging parties in order to succeed in the integration and to avoid resistance and decreased performance in the new, merged company. The paper contributes to the continuum of research on dialectical tensions but brings a new context, that of international mergers and acquisitions, to this continuum. Nor has the concept of organisational identity been researched earlier in relation to dialectical tensions.